2017
DOI: 10.1111/aab.12375
|View full text |Cite
|
Sign up to set email alerts
|

Aspects in oat breeding: nutrition quality, nakedness and disease resistance, challenges and perspectives

Abstract: Traditionally, the oat crop (Avena sativa) has been neglected in a number of respects, cultivated in cropping areas not optimal for wheat, barley or maize. In recent years the interest in oats has increased, particularly because of its dietary benefits and therapeutic potential for human health. The uniqueness and advantages of naked oats over other popular cereals, due to its potentially valuable nutritional composition, have been well studied and reported, opening new market “niches” for oats. Despite the we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 157 publications
0
43
0
1
Order By: Relevance
“…The selection gain for grain weight could be attributed to the correlated selection response for grain yield, whereas grading appeared as an important selection criterion as most of the naked oats were discarded. For naked oats less breeding effort has been undertaken, resulting in a comparable low number of released varieties [59,60]. Therefore, this type has only regionally a niche market [57,59].…”
Section: Breeders' Decisions and Selection For Local Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection gain for grain weight could be attributed to the correlated selection response for grain yield, whereas grading appeared as an important selection criterion as most of the naked oats were discarded. For naked oats less breeding effort has been undertaken, resulting in a comparable low number of released varieties [59,60]. Therefore, this type has only regionally a niche market [57,59].…”
Section: Breeders' Decisions and Selection For Local Adaptationmentioning
confidence: 99%
“…For naked oats less breeding effort has been undertaken, resulting in a comparable low number of released varieties [59,60]. Therefore, this type has only regionally a niche market [57,59]. All black oats were discarded as well, as there is generally no market for this germplasm in Estonia or the Czech Republic, where the accessions were tested.…”
Section: Breeders' Decisions and Selection For Local Adaptationmentioning
confidence: 99%
“…In the past, oats were mainly treated as a phytosanitary plant or planted for horse feeding purposes (Gorash et al 2017). Currently, oat grain is increasingly used in the food industry due to its rising use in exclusion diets, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, oat varieties with different chemical composition are used in oat cultivation (Gorash et al 2017). Research is also being conducted on the improvement of quality and increase in yield of varieties containing bioactive compounds (Kawka and Achremowicz 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, oat production is decreasing despite the crop has great nutritional and therapeutic values. Gorash et al [8] reported that oat crop traditionally has been neglected in a number of respects, cultivated in non-optimal cropping areas as wheat, barley or maize. Lin et al [9] reported oat actual evapotranspiration (ETc) range of 227 -305 mm and water productivity that varied from 1.03 to 1.2 kg/m 3 under conventional irrigation and alternative partial root zone irrigation in Baicheng city, Jilin province of China.…”
Section: Introductionmentioning
confidence: 99%